Galloyl esters of trans-stilbenes are inhibitors of FASN with anticancer activity on non-small cell lung cancer cells - Tan, Yu-Jia (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2022)
10.1016/j.ejmech.2019.111597